Operational Deficiencies in rural gastronomic establishments: Case Mindo: Deficiencias Operativas en establecimientos gastronómicos rurales: Caso Mindo - Proaño Varela, Jonathan Santiago (2019)
The present investigation was carried out in the rural parish of Mindo and aims to identify the main operational failures in collective feeding establishments. The article addresses central issues such as food handling, handler hygiene and facilities, waste management and inadequate personnel work habits. The results show a constant in the factors related to personnel practices, which affect a problem in food preparation operations, regarding the food contamination risk, product waste and unhealthiness of gastronomic services facilities. Nowadays, the tourism offer worldwide is characterized by socio-environmental responsibility and the dynamics of fair trade, Ecuador is a destination that has these indicators of value, despite the need for training in aspects related to good management of food and services. To demonstrate this reality, an exploratory study was carried out in which operational deficiencies are highlighted at food retail sites in the tourist center of the rural parish of Mindo, Pichincha province.